Semantics of blasphemy against the holy Prophet and how it is realized with a view to the Islamic Penal Code 2013 - ???? ????, ???????; ????? ????, ????; ??????? ???? ????, ???????? (??? ? ????)
The crime of blasphemy against the holy Prophet is a significant crime against religion in the recognized literature of Islamic jurisprudence in a way that it leads to capital punishment and each Muslim hearing the blasphemy can execute the penalty. The Islamic Penal Code, in articles 262 and 263 and 513 of the discretionary penalties (Tazirat) has described this crime. Nevertheless, there are questions and ambiguities about this crime, e.g. how and with what words, this verbal crime is committed? In addition, is the word the mere object of the crime or act, caricature, drawing, clip, joke, animation and novel may result in the above said crime? The present paper, through relying on Islamic jurisprudence evidence and Islamic jurists' opinions and rational arguments and reasons, is intended to study the semantics of blasphemy against the holy Prophet and offer a criterion of the realization of its actus reus.